Analisis Risiko Kecelakaan Kerja Menggunakan Metode Job Safety Analysis (JSA) di CV. Budidaya Jamur Sejati - Fauzi, M Rifqi; Mustaqim, Mustaqim; Hamida, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
CV. Budidaya Jamur Sejati is one of the production industries of oyster mushrooms, which processes through planting and nurturing oyster mushrooms or (Pleurotus ostreatus) to grow and develop optimally for harvesting and selling. Oyster mushrooms are popular to cultivate because they have a delicious taste, high nutritional value, and the cultivation process is relatively easy and inexpensive. In every stage of oyster mushroom production, there are several risks of worker accidents that require further handling. Therefore, to identify the factors and causes of accidents and to assess the potential and risks involved, efforts are then made to control these using Job Safety Analysis methods to minimize workplace accidents at each stage. This results in accidents with extremely high risk during the sterilization stage of the growing medium, where hot steam from the sterilization process can cause burns to the workers' hands during heating.